2013
DOI: 10.1371/journal.pone.0063349
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence of Batrachochytrium dendrobatidis in Contemporary and Historical Samples of the Endangered Bombina pachypus along the Italian Peninsula

Abstract: Batrachochytrium dendrobatidis is considered a main driver of the worldwide declines and extinctions of amphibian populations. Nonetheless, fundamental questions about its epidemiology, including whether it acts mainly as a “lone killer” or in conjunction with other factors, remain largely open. In this paper we analysed contemporary and historical samples of the endangered Apennine yellow-bellied toad (Bombina pachypus) along the Italian peninsula, in order to assess the presence of the pathogen and its sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 62 publications
1
21
3
Order By: Relevance
“…Thus, our observation in the yellowbellied toad population Baumbach marl pit/Hergerhausen stone pit with high prevalence of Bd but population growth confirms that of Tobler et al (2012), who also concluded that observed negative effects of Bd on survival of individuals do not necessarily translate into negative effects at the population level. In yet another study, Canestrelli et al (2013) showed that Bd has been present in Apennine yellow-bellied toad populations Bombina pachypus at least since the late 1970s, but strong declines only started after the mid-1990s. From this, the authors concluded that Bd cannot be the only reason for declines but possibly interacts with other stressors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, our observation in the yellowbellied toad population Baumbach marl pit/Hergerhausen stone pit with high prevalence of Bd but population growth confirms that of Tobler et al (2012), who also concluded that observed negative effects of Bd on survival of individuals do not necessarily translate into negative effects at the population level. In yet another study, Canestrelli et al (2013) showed that Bd has been present in Apennine yellow-bellied toad populations Bombina pachypus at least since the late 1970s, but strong declines only started after the mid-1990s. From this, the authors concluded that Bd cannot be the only reason for declines but possibly interacts with other stressors.…”
Section: Discussionmentioning
confidence: 98%
“…However, deadly chytridiomycosis in captive toads has been previously observed and was thought to be responsible for declines (Stagni et al 2004). Hence, a role for Bd in the widespread decline of the Apennine yellow-bellied toad still appears plausible (Canestrelli et al 2013), and it could be hypothesized that the closely related B. variegata is also suceptible under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For our study species, this assumption is justified by the relative tolerance to the pathogen observed in B. variegata, where populations are known to have persisted in the presence of chytrid for several years (Canestrelli et al 2013), suggesting that infected and uninfected individuals will not exhibit important differences in behavior (hence our reference to pathogen prevalence, rather than disease prevalence). However, this assumption may be violated for other species, and lead to different recapture rates: for example, altered behavior may render infected individuals more likely to be captured.…”
Section: Discussionmentioning
confidence: 99%
“…Populations in the north and center of the species' range have declined in both number and abundance since the mid-1990s (Barbieri et al 2004). A recent study has found evidence of infection by B. dendrobatidis on specimens across the Italian peninsula (Canestrelli et al 2013). Other subspecies of Bombina variegata are prone to infection by B. dendrobatidis (Spitzen-van der Sluijs et al 2011, Sztatecsny andGlaser 2011), and mortality resulting from chytridiomycosis has been recorded for B. v. pachypus originating from two populations in the northeastern Apennines (Stagni et al 2004).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation